Evaluasi Kesiapan Kader Keamanan Pangan Desa dengan Penerapan Sistem Pembelajaran Elektronik (E-Learning) - Winiati P. Rahayu; Ruki Fanaike; Salma Nur Adillah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2022)
The development of the Villages Food Safety Movement Program requires learning materials which are easy-to-understand and accessible for Village Food Safety Cadres (KKPD). The number of respondents were 16 person for three groups of respondents which were eight persons of PKK member, four persons of teacher, and four persons of neighborhood youth association member. They were divided into two group which were telefon gengam and laptop group. The result showed that only a design of the food safety introduction module in the mobile phone group (25.0%) was good, while the other 75.0% were very good. The design and material content from other modules were scored very good. Respondents’ knowledge scores after training showed an increase in 13 points (52.00%), 11 statements were remain same (44.00%), and there were a decrease in 1 statement (4%). Generally, KKPD mobile phone group had the readiness in terms of technology, human resource, and innovation but for laptop group has to increase in term of human resource factor.